Pelatihan Pembuatan Media Augmented Reality Menggunakan Aplikasi Assemblr Edu pada Pembelajaran IPA Bagi Guru Madrasah Ibtidaiyah di Kota Bogor - Rahmawati, Ima; Hana Lestari; Ria Rizki Agustini (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to evaluate the effectiveness of training in creating Augmented Reality (AR) media using the Assemblr Edu application for teachers in Madrasah Ibtidaiyah (MI) in Bogor City, focusing on science education. The method employed is Participatory Action Research (PAR), involving 30 teachers from various MIs. An initial survey revealed that 60% of the teachers lacked knowledge about AR, while 80% expressed interest in learning more. After the training, evaluation questionnaires indicated that 90% of participants found the training very beneficial, and 85% were able to effectively create AR media. Furthermore, the evaluation of student learning outcomes showed an increase in average scores from 65 before the AR implementation to 78 afterward, reflecting a 20% improvement in student understanding. Qualitative data from interviews and classroom observations highlighted increased student enthusiasm and more active interactions between students and teachers, aligning with constructivist theory and multimedia learning theory. Despite challenges such as technical difficulties and inadequate infrastructure, recommendations for ongoing technical support and improved access to technology are essential. This research emphasizes the potential of AR as an innovative tool in education, capable of enhancing the quality of learning in MIs and opening avenues for further research on the application of modern technology in education in Indonesia.